2004
DOI: 10.1080/08958370490476550
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Retention of Particulate Matter is Associated with Airway Inflammation in Allergic Rats Exposed to Air Pollution in Urban Detroit

Abstract: A collaborative research study was conducted in order to improve our understanding of the source-to-receptor pathway for ambient fine particulate matter (aerodynamic diameter < or = 2.5 mu m; PM2.5) and subsequently to investigate the identity and sources of toxic components in PM2.5 responsible for adverse health effects in allergic humans. This research used a Harvard fine particle concentrator to expose Brown Norway rats, with and without ovalbumin-induced allergic airway disease, to concentrated air partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
3
24
0
1
Order By: Relevance
“…However, while some studies have shown that inhaled ultrafi ne carbon particles (Andre et al 2006 ) or CAPs (Lei et al 2004 ) can also lead to increased infl ammatory cell counts in the BALF or increased infl ammatory cytokines (Kampfrath et al 2011 ), others have shown no effects on either BALF cell counts, histology or lung pro-infl ammatory gene expression (Gunnison and Chen 2005 ;Ito et al 2008 ;Heidenfelder et al 2009 ). These different responses could be due to the variability in CAPs composition or length of exposures (Saldiva et al 2002 ;Morishita et al 2004 ). Consistent with the latter, we have observed that DE for 2 weeks (Yin et al 2013 ) or CAPs for 5 weeks (Araujo et al 2008 ) did not result in the development of obvious pulmonary infl ammation (Araujo et al 2008 ;Yin et al 2013 ), but clearly led to lipid and pro-atherogenic effects, respectively.…”
Section: Role Of the Lungs In Mediating Systemic Effectssupporting
confidence: 81%
“…However, while some studies have shown that inhaled ultrafi ne carbon particles (Andre et al 2006 ) or CAPs (Lei et al 2004 ) can also lead to increased infl ammatory cell counts in the BALF or increased infl ammatory cytokines (Kampfrath et al 2011 ), others have shown no effects on either BALF cell counts, histology or lung pro-infl ammatory gene expression (Gunnison and Chen 2005 ;Ito et al 2008 ;Heidenfelder et al 2009 ). These different responses could be due to the variability in CAPs composition or length of exposures (Saldiva et al 2002 ;Morishita et al 2004 ). Consistent with the latter, we have observed that DE for 2 weeks (Yin et al 2013 ) or CAPs for 5 weeks (Araujo et al 2008 ) did not result in the development of obvious pulmonary infl ammation (Araujo et al 2008 ;Yin et al 2013 ), but clearly led to lipid and pro-atherogenic effects, respectively.…”
Section: Role Of the Lungs In Mediating Systemic Effectssupporting
confidence: 81%
“…Previously, our group has shown that pulmonary exposure to particulate zymosan increased lung neutrophil influx, LDH activity, and alveolar macrophage activation [26]. Others have shown that different lung pro-inflammatory agents, such residual oil fly ash [31,32], diesel exhaust particles [33], ambient particulate matter [34,35], and house dust mites [36] have adjuvant effects in animal respiratory allergy models.…”
Section: Resultsmentioning
confidence: 99%
“…Moss was used as well for similar purposes [76]. Pulmonary retention of particulate matter in the lung tissues of exposed rats was used both as evidence for the transport of particles and specific effects (allergic reactions) of toxic substances on organisms [77]. Bioaccessibility of trace metals originating from urban particulate matter was assessed in a worst case scenario to evaluate the uptake and thus the hazardous potential of these metals via gastric juice.…”
Section: Methods Developmentmentioning
confidence: 99%